2014
DOI: 10.1002/pbc.25195
|View full text |Cite
|
Sign up to set email alerts
|

Family life events in the first year of acute lymphoblastic leukemia therapy: A children's oncology group report

Abstract: Background Despite higher cure rates, childhood acute lymphoblastic leukemia (ALL) may continue to result in considerable family strain. We sought to (i) measure incidence of divorce, reduced career opportunities, changes to work hours, home relocation, and changes to family planning at one year after ALL diagnosis; and (ii) Identify family and patient factors associated with these events. Procedure We conducted a prospective cohort study of 159 children with average risk-ALL enrolled and treated on COG prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
3
26
0
9
Order By: Relevance
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Managing the child's disease and treatment alongside everyday responsibilities can be highly challenging for parents. Several studies demonstrated that treatment‐related work disruptions such as time off work, quitting or reducing workload are frequent among parents of patients with childhood cancer . These work disruptions resulted in substantial income losses .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies document that children diagnosed with cancer experience various forms of distress associated with the cancer experience . Cancer and its associated treatment can have a serious social and emotional impact on the child and the parent . Much data indicate that child functioning is closely associated and often dependent on parent and family functioning .…”
Section: Resultsmentioning
confidence: 99%